Synopsis of hand surgery - LaPorte, Dawn (Thieme, 2021)
"Hand surgery emerged as a specialty due to advances in treatment of hand injuries incurred during World War II. Synopsis of Hand Surgery by distinguished hand surgeon Dawn LaPorte reflects the approach championed by the late American surgeons Sterling Bunnell and Norman Kirk: multidisciplinary care is key to optimal treatment of bone and soft tissue conditions in the hand and wrist. The book features contributions from an impressive group of hand and upper extremity surgeons and radiologists"--